Thermal radiation and thermo-diffusion in Casson-ferrofluid over a magnetized porous surface: RSM analysis - S. Manjunatha; J. Santhosh Kumar; Khalil Ur Rehman; Wasfi Shatanawi; S.V.K. Varma (International Journal of Thermofluids)
A wide variety of heat transfer applications employ ferrofluids. These include heat exchangers, materials research, and a host of other industries, such as food processing, solar trough collectors, and aerospace engineering. The main goal of this study is to investigate how fluid moves through a porous medium stretched across a Casson ferrofluid bilinear stretching surface, accounting for the effects of slip and magnetic fields. This study takes into account factors such as thermal radiation, heat source/sink, first-order chemical reactions, Soret, and Dufour effects. Similarity transformations convert the flow model's governing nonlinear coupled partial differential equations into ordinary coupled differential equations. The results are obtained using the time-saving bvp4c approach in MATLAB along with the shooting technique and presented in graphs and tables. The derived quantities, namely skin friction, Nusselt number, and Sherwood number at the stretching surface, are also computed. The effects of various parameters on flow-derived quantities have been analyzed and discussed. The momentum boundary layer drops as the Casson parameter rises. As the magnetic parameter raises, the fluid velocity drops, while the fluid temperature exhibits the opposite phenomenon. As radiation and heat sources increase, the temperature rises, whereas the Dufour effect leads to the opposite outcome. The adjusted R-squared and R-squared for skin friction achieve a value of 99.92 %. Compared to the Dufour effect, the Nusselt number is more affected by the heat source and thermal radiation parameter. Some important contributions include discussing response surface methods and studying the complex connections between Casson fluid, porosity, and the stretching ratio parameter.